Assessing the Reliability of Planktic Foraminifera Ba/Ca as a Proxy for Salinity off the Sunda Strait - Riza Yuliratno Setiawan; Anindya Wirasatriya; Hasrizal Bin Shaari; Eko Setyobudi; Faizal Rachman (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
The Ba/Ca ratio of planktic foraminifera carbonate serves as a new geochemical proxy for seawater Ba/Ca and thus providing information on modern and past salinity and freshwater discharge. In this study the applicability of Ba/Ca ratio of core-top Globigerinoides sacculifer collected off the eastern tropical Indian Ocean (ETIO) for paleoceanographic reconstructions was investigated. In doing so, we conducted a series of cleaning experiments for Ba/Ca extraction by using different reductive solutions. Our new results suggest that the Ba/Ca ratio of G. sacculifer cannot be utilized as a tracer for modern and past salinity changes in the ETIO region off the Sunda Strait. We suggest that the existence of seasonal upwelling adds an additional signal to the seawater Ba/Ca in the ETIO, and thus complicates the interpretation of G. sacculifer Ba/Ca as a freshwater tracer. Moreover, our cleaning experiment results show that the cleaning protocol of Mg/Ca, DTPA, and hydroxylamine can be used to extract valuable Ba/Ca ratios from planktic foraminifera tests. Keywords: G. sacculifer Ba/Ca, foraminifera cleaning experiments, the Sunda Strait.